IBIS Management System - Nurain Aleeya, Che Zaharudin (2023)
The IBIS Management system is an extensive system designed to manage various organisational aspects, such as registration, financial management, maintenance tasks, and report generation. The registration module of the system enables effective management of new user registration, including data collection for personal and contact details as well as account management. The financial management module enables the management of income and expenses, and the creation of financial reports. The management of maintenance tasks, including scheduling, tracking of progress, and reporting, is made possible by the maintenance activity module. The system also has a module for creating reports that can be used to analyse different aspects of how the organisation operates, such as its financial performance, upkeep tasks, and user registration. The user-friendly interface of the IBIS Management system makes it simple to navigate and offers a thorough overview of the organization's operations. It will support enhancing an organization's performance overall, productivity, and efficiency.